Math, asked by sirs7007, 5 months ago

CLASS X MATHS...


1.If a and B are two zeroes of the polynomial x²-2x-15 then form a quadratic polynomial
whose zeroes 2a and 2B.


Kindly don't spam!!​

Answers

Answered by Anonymous
11

Answer:

Given : If α and β are zeroes of the polynomial x²-2x-15

Need To Find : A quadratic polynomial whose zeroes 2α and 2β.

⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀

❍ First Find out all Cofficients of Given Polynomial x²-2x-15 :

  • Cofficient of x² = 1 .
  • Cofficient of x = -2 .
  • Constant Term = -15 .

⠀⠀⠀⠀⠀ As , We know that α and β are two zeroes of Polynomial x²-2x-15 .

As, We know that :

⠀⠀⠀⠀⠀\implies \sf{\alpha + \beta = \dfrac{- Cofficient \:of\:x \:}{Cofficient \:of\:x^{2} }}\\

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\underline {\frak{\star\:Now \: By \: Substituting \: the \: Cofficients\::}}\\

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\implies \tt{\alpha + \beta  = \dfrac{-(-2) \:}{1 }}\\

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\implies \tt{\alpha + \beta = \dfrac{2 \:}{1 }}\\

Or ,

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\implies\boxed {\sf{\alpha + \beta  = 2 \:}}\:\bf{\star}\\

As, We know that :

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀\implies \sf{\alpha \times \beta = \dfrac{Constant\:Term \:}{Cofficient \:of\:x^{2} }}\\

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\underline {\frak{\star\:Now \: By \: Substituting \: the \: Cofficients\::}}\\

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\implies \tt{\alpha  \times \beta = \dfrac{-15 \:}{1 }}\\

Or ,

⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀⠀\implies\boxed {\sf{\alpha \times \beta = -15 \:}}\:\bf{\star}\\

⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀

As, We know that ,

  • Quadratic Polynomial = x² - (sum of zeroes ) x + Product of zeroes

⠀⠀⠀⠀⠀

Given that :

  • The zeroes of new formed polynomial will be 2α and 2β .

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀\underline {\frak{\star\:Now \: By \: Substituting \: the \: Given \: Values \::}}\\

⠀⠀⠀⠀⠀

⠀⠀⠀⠀⠀⠀:\implies {\tt{  \bigg( x^{2} - ( 2\alpha + 2\beta ) x+  ( 2\alpha \times 2 \beta ) \bigg) }}\\

⠀⠀⠀⠀⠀⠀:\implies {\tt{  \bigg( x^{2} -2 ( \alpha + \beta ) x +( 2\alpha \times 2 \beta ) \bigg) }}\\

⠀⠀⠀⠀⠀⠀:\implies {\tt{  \bigg( x^{2} -2 ( \alpha + \beta ) x  + 4\alpha\beta  \bigg) }}\\

As , We have found ,

\implies \tt{\alpha  \times \beta = -15 \:}\\

\implies \tt{\alpha + \beta =  2 \:}\\

⠀⠀⠀⠀⠀⠀:\implies {\tt{  \bigg( x^{2} -2 ( 2 ) x + 4(-15)  \bigg) }}\\

⠀⠀⠀⠀⠀⠀:\implies {\tt{  \bigg( x^{2} -4x -60  \bigg) }}\\

Or ,

⠀⠀⠀⠀⠀⠀:\boxed{\sf{ New\:Formed \:Quadratic \:Polynomial  = x^{2} -4x -60   }}\\

⠀⠀⠀⠀⠀

Therefore,

⠀⠀⠀⠀⠀⠀ \therefore \underline{\sf{ New\:Formed \:Quadratic \:Polynomial  = x^{2} -4x -60   }}\\

⠀⠀⠀⠀⠀━━━━━━━━━━━━━━━━━━━⠀

Similar questions